(untitled) (مجلة جامعة سرت للعلوم الانسانية, 2023)
The study aimed to identify the level of psychological stress among faculty members in some faculties of Al Asmariya Islamic University, and to identify the level of quality of life among faculty members, and to identify whether there is a statistically significant relationship between psychological stress and quality of life among faculty members, and to identify the level of quality of life among faculty members. Whether there are differences in psychological stress among faculty members due to the variable years of experience, academic degree, and gender, and to identify whether there are differences in the quality of life among faculty members due to the variable years of experience, academic degree, and gender, as the researcher used the descriptive approach in This study is appropriate to the nature of the research, and to achieve the objectives of the study, the researcher applied a questionnaire to all members of the study community, which consisted of (138) faculty members. teaching, and there is an inverse correlation between the psychological pressures that a faculty member is exposed to and the quality of life of faculty members, and there is a difference between the scientific degrees of members who are The teaching class is at the level of the pressures that the faculty member is exposed to, so that those who hold the academic degree of associate professor are less vulnerable to psychological stress, and the different educational degrees of the faculty members have no effect on the level of quality of life that they live.